Advances in environmental remote sensing : sensors, algorithms, and applications - Weng, Qihao (Taylor & Francis series in remote sensing applications series., 2011)
"Featuring contributors from 17 countries, this book systematically presents recent advances in environmental remote sensing. First, the text provides the latest developments in remote sensing data and sensor systems, paying special attention to LIDAR, hi